Neurological soft signs in schizophrenia spectrum disorders are not confounded by current antipsychotic dosage - Fritze, Stefan; Kubera, Katharina Maria; Wolf, Robert Christian; Hirjak, Dusan (European neuropsychopharmacology, 2020)
Neurological soft signs (NSS) have garnered increasing attention in psychiatric research on motor abnormalities in schizophrenia spectrum disorders (SSD). However, it remains unclear whether the assessment of NSS severity could have been confounded by current antipsychotic dosage. In this study, we recruited 105 patients with SSD that underwent a comprehensive motor assessment evaluating NSS and extrapyramidal motor symptoms (EPMS) by means of standardized instruments. Current antipsychotic dosage equivalence estimates were determined by the classical mean dose method (doses equivalent to 1 mg/d olanzapine). We used multiple regression analyses to describe the relationship between NSS, EPMS and antipsychotic medication. In line with our expectations, current antipsychotic dosage had no significant effects on NSS total score (p = 0.27), abnormal involuntary movements (p = 0.17), akathisia (p = 0.32) and parkinsonism (p = 0.26). Further, NSS total score had a significant effect on akathisia (p = 0.003) and parkinsonism (p = 0.0001, Bonferroni corr.), but only marginal effect on abnormal involuntary movements (p = 0.08). Our results support the notion that NSS are not significantly modulated by current antipsychotic dosage in SSD. The associations between NSS, akathisia and parkinsonism, as revealed by this study, support the genuine rather than medication-dependent origin of particular motor abnormalities in SSD.